HUBUNGAN PENGGUNAAN TUSUK GIGI TERHADAP TERJADINYA SAKU GUSI PADA MASYARAKAT DUSUN II DESA MARINDAL II KECAMATAN PATUMBAK KABUPATEN DELI SERDANG TAHUN 2016 - Kartika Emailijati; Adriana Hamsar; Etty M. Marthias; Nurul Aini (Jurnal Kesehatan Gigi, 2016)
TITLEThe relationship between toothpick usage and gingival pocket on society of Dusun II, Desa Marindal II, Patumbak, Deli Serdang in 2016ABSTRACTToothpick is a piece of wooden or plastic stick used to remove food accumulated from teeth. The improper use of toothpick can damage the soft tissues around the tooth and cause inflammation on the mucosa tissue of the oral cavity. The preliminary survey conducted in Dusun II, Mariendal II Village, Patumbak Sub-district found that 25% of the residents who used toothpick complaint about bleeding gum and gap-tooth.This is an analytical research with case control method with population of 520 people. The samples were 52 respondents who were divided into two groups; the first 26 respondents used toothpick and the other 26 respondents did not use toothpick.The results showed that the uses of toothpick may cause periodontal pocket compared to the group who did not use them. It could be seen from the score difference for CPITN (Community Periodontal Index of Treatment Needs), the highest score indicated by the group that used toothpick was 3 which was represented by 53.8% and the highest score obtained by the group that did not use toothpick was 2 which was represented by 73.1%. The statistical analysis with chi-square test gained probability value 0.0001 (p0.05). In conclusion, H0 was rejected which meant that there was a correlation between the uses of toothpick and the incidence of periodontal pocket. Key words : Toothpick, Periodontal Pocket